2021
DOI: 10.1016/j.bpr.2021.100034
|View full text |Cite
|
Sign up to set email alerts
|

Recharging your fats: CHARMM36 parameters for neutral lipids triacylglycerol and diacylglycerol

Abstract: Neutral lipids (NLs) are an abundant class of cellular lipids. They are characterized by the total lack of charged chemical groups in their structure, and, as a consequence, they play a major role in intracellular lipid storage. NLs that carry a glycerol backbone, such as triacylglycerols (TGs) and diacylglycerols (DGs), are also involved in the biosynthetic pathway of cellular phospholipids, and they have recently been the subject of numerous structural investigations by means of atomistic molecular dynamics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…Campomanes et al found that the CHARMM36 parameters for TAG and DAG molecules were too hydrophilic in the glycerol−ester region and reparameterized the charges. 35 This agrees with our finding that, with the current CHARMM36, TAG starts to aggregate at a much higher concentration than the ones reported in experiments. Therefore, we note that the nonbonded parameters can impact the simulation results, and a careful treatment of the force field parameters will further pave the road for development in this field.…”
Section: Perspective Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Campomanes et al found that the CHARMM36 parameters for TAG and DAG molecules were too hydrophilic in the glycerol−ester region and reparameterized the charges. 35 This agrees with our finding that, with the current CHARMM36, TAG starts to aggregate at a much higher concentration than the ones reported in experiments. Therefore, we note that the nonbonded parameters can impact the simulation results, and a careful treatment of the force field parameters will further pave the road for development in this field.…”
Section: Perspective Discussionsupporting
confidence: 92%
“…Their MK9 parametrization has more polar carbonyl groups and a smaller van der Waals radius for hydrogen atoms than the CHARMM36 FF. Campomanes et al found that the CHARMM36 parameters for TAG and DAG molecules were too hydrophilic in the glycerol–ester region and reparameterized the charges . This agrees with our finding that, with the current CHARMM36, TAG starts to aggregate at a much higher concentration than the ones reported in experiments.…”
Section: Perspective Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…14 It is important to note that these magnitudes of hydration are likely overestimated since the standard CHARMM36 parameters used in our model for TG are not ideal for bulk hydration properties and interfacial (water/lipid) surface tension. 33,34 The central limitation in these, and all parameters developed to date, is lack of polarizability, which is essential to capture proper neutral lipid interactions in both nonpolar core and polar interfacial environments. For example, bulk TG is hydrophobic, but at a water interface the glycerol moieties should have larger partial charges in response to proximal water.…”
Section: Resultsmentioning
confidence: 99%
“…10,36,37 Updates to the additive forcefields of TG that correct bulk hydration and interfacial water/lipid surface tension do not correctly represent the APL of a LD monolayer, likely due to increased hydrophobicity that retains TG in the LD core. 38,39…”
Section: Resultsmentioning
confidence: 99%